DOES IT MATTER HOW THE STUDENTS FEEL? PRACTICAL IMPLICATIONS OF SOCIAL RELATIONSHIPS IN SCHOOL - Matric, Maja (Journal of process management and new technologies, 2018)
School cannot be merely defined as a content-learning environment, but also a context in which pupils learn social behaviour (Košir, 2013), which brings into question the role of social relationships in school. This is reflected in a growing number of research in the area of educational psychology examining the learning process beyond the cognitive scope, by establishing the role of peer relationships, social acceptance and other elements of social relationships in education (Pellegrini, & Blatchford, 2000). Because of this, we cannot simply overlook the importance of social relationships children form within their peer groups. In the article, we include an overview of theoretical approaches which firmly place social relations in the learning process, and support these notions with relevant research literature. We also include practical guidelines and approaches which should prioritize social relationships in the making of positive school climate.